The experience of meaning and writing - Jonkus, Dalius (Religija ir kultūra, 2008)
This article analyses the relationship of the experience of meaning with writing. Is the intuition of meaning or the recording of it more important in scientific discovery and tradition? The goal of this article is to show that the relation of the experience of meaning and writing can be understood only from a perspective where transcendentalism and empiricism meet. Derrida accentuates writing as the opposite of voice, but forgets that writing must be correlated with the experience of meaning. Husserl understood the art of writing as the empirical articulation of ideal meanings. Writing is a passive sedimentation of the experience of meaning, which must be re-activated and re-realised. Writing is a risky activity, which does not set one free from a contingent world, but forces one to accept responsibility.
Keywords: meaning; experience; writing; phenomenolgy